The endogeneity of optimum currency areas criteria: European Union, Euro Zone and the Portuguese case - Silvestre, João (2022)
Six years after the monetary unification in Europe is still too early to provide a definitive evaluation of its consequences but it is possible to find some evidences. Observing the statistical relationship between business cycles correlation and trade intensity in European Union, Euro zone and the Portuguese economy we conclude that there is, in general, a positive effect that supports the endogeneity argument proposed by Frankel and Rose (1998). However, if we analyse this relation in sub-periods - 1967-1975, 1976-1985, 1986-1992 and 1993-2003 – we conclude that endogeneity hypothesis just hold in the first two, although the correlations are increasing. This could mean that, after Single European Act (1986), other forces beyond trade are contributing to business cycle synchronization. The Portuguese business cycle correlation with European Union and Euro zone had also increased in these four decades, despite the fact that endogeneity hypothesis just hold with a 90% confidence level. In this case, exports seem to be the most important trade flow explaining the economic synchronization. The 2 R of the regressions are very low and, for that reason, we can conclude that even with endogeneity hypothesis confirmed there are other variables explaining business cycles correlation.